“Test of Competence in Science and Technology,” a model of external evaluation in Spain - Martín-Páez, Tobías; Vílchez-González, José Miguel; Carrillo-Rosúa, Francisco Javier (Education Policy Analysis Archives, 2019)
This research focuses on the analysis of the “Test of competence in science and technology” developed as a model test for the Grade 6 by the Spanish Ministry of Education, Culture and Sport (MECD). The analysis focuses on checking whether the “Test of Science and Technology Competence” conforms to its theoretical frameworks of reference, as well as to characterize the presence of scientific competence in the items of the same. This is a descriptive exploratory documentary research, which use an instrument designed in accordance to the General Framework of Primary Education Final Assessment; four teaches perform as observers. The results allow us to conclude that the distribution of some of the analyzed variables does not conform to what is demanded in the reference frameworks and that the subcompetences associated with scientific competence in the international evaluation frameworks do not appear in the test equitably. It is finalized with improvement proposals for future evaluations test.